Optimization of satellite-based communication links. - Bilal Muhammad Khan; Muhammad Raheel (PLoS ONE)
Satellite communication (SATCOM) is crucial for global connectivity, particularly in remote far-flung areas. Typically, these links are established by connecting a Satcom Remote Terminal to a Satcom Hub Station. However, relying on a single Hub Station does not offer redundancy, leaving remote terminals isolated in case of a Hub Station failure. To provide redundancy, the remote terminals are shifted to a secondary Hub Station. However, several limitations and challenges are associated with the available methodologies for shifting of remotes to the secondary Hub Station. This research addresses the challenges associated with the implementation of redundancy/ Disaster Recovery (DR) mode in a Satcom Network to improve reliability and efficiency of Satcom links. An optimized model has been developed for Satcom Remote Modems to automatically switch to a secondary Hub Station during a primary Hub Station failure. The technique was tested in a real Satellite Communication Network, showing improved results compared to traditional methods.